Revolution at the margins : the impact of competition on urban school systems - Hess, Frederick M. (Brookings Institution Press, 2002)
"Urban school systems have a difficult mandate: to educate large numbers of disadvantaged children under the heavy hand of often dysfunctional managerial, accountability, and regulatory systems." "Over the past decade they have also been challenged - in some cases threatened - by competition from school vouchers and charter schools." "Revolution at the Margins examines how urban school systems are responding to education competition. Drawing on case studies conducted in three school districts at the center of the school choice debate, the book seeks to clarify how competition is likely to play out in urban education; shed light on the ways in which system structure and practice hamper efforts to improve urban schooling; and better understand what promise market-driven reform holds for the future of children's education."--Jacket